The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12691/ajnr-7-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Scenario Based Learning in Critical Care Nursing Education: Students’ Achievement and Feedback

Abstract: Scenario based learning (SBL) is up-to-date inventive teaching method that providing directive discussion for nursing students. Effective designed scenarios are considered the corner stone for teachers to integrate learning objectives into nursing students' learning experience. Many studies reported that SBL is a broad dynamic interactive teaching and learning strategy. It enhances students' decision making skills and self-learning abilities. Aim: the current study aimed to explore fourth level nursing student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In agreement with our results from both quantitative and qualitative data, many previous studies have reported that scenario-based education expands student knowledge and awareness and improves their learning abilities and analytic skills. 2 , 9 Another study, by Hudson and Ozsevgec, investigated the effectiveness of simulation-based learning in learning and overcoming student misconceptions and also found that simulation-based learning strategies had a considerably positive effect on the achievement of students. 13 , 19 Our results are also consistent with those of Amorim et al., who reported that students perceived realistic simulation in a pediatric emergency as an effective teaching approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with our results from both quantitative and qualitative data, many previous studies have reported that scenario-based education expands student knowledge and awareness and improves their learning abilities and analytic skills. 2 , 9 Another study, by Hudson and Ozsevgec, investigated the effectiveness of simulation-based learning in learning and overcoming student misconceptions and also found that simulation-based learning strategies had a considerably positive effect on the achievement of students. 13 , 19 Our results are also consistent with those of Amorim et al., who reported that students perceived realistic simulation in a pediatric emergency as an effective teaching approach.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Finally, another study demonstrated that simulation-based learning was a dynamic learning strategy for critical care nursing students as it enhanced appraisal skills and learning abilities. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many authors emphasize that this method strengthens students’ abilities and skills in analytical thinking, problem solving, communication and teamwork [ 5 ]. This improves self-reliance [ 6 ] and self-learning skills [ 7 ]. The available evidence suggests that the use of one teaching model, even a new model, is not enough to promote learning.…”
Section: Introductionmentioning
confidence: 99%